Lightning company / Luqman Hakim Saimil...[et al.] - Saimil, Luqman Hakim; Zulkifli, Azfarizzatul Aniqah; Ariffin, Anis Afiqah; Zainudin, Nurfarzana; Abdullah, Siti Nur Alia
Lightning Company /have jdeveloped a new product to introduce to the consumers which called as Lightning Deep Fryer. Our company targeting in supply for Lightning Deep Fryer since it is can be used by people that owned a restaurant to cook more efficiently. Next, Lightning Deep Fryer is a customerfriendly which helps people save time and ease them to fry and cook food. As many years passed by, technology development grow rapidly and more costing. Nowadays, people might think that it is difficult to start a business based on food and beverages because they cannot afford to buy those kind of technology such as deep fryer that is increasingly sophisticated. Therefore, Lightning Deep Fryer can help the consumer to have deep fryer that are affordable and easy to use. Overall marketing strategy will be included specific marketing philosophy and strategy of the company, the value chain and the channel of distribution in the target market. First of all, our target market will be based on the residence in Shah Alam area since our company was nearby Shah Alam. For initial intensive selling effort, our company has set the target customers in other words, types of customer groups that would buy our product. Our target customer is for restaurant owner, stalls. The lastly, our target customer is the family residence. The product is designed to save time, biodegradable, and help workers to cook faster and consistent. It will ease and minimise the time for the chef that are always needed to serve food faster and at the same to keep maintain the food quality and consistency. The price is reasonable and there is two energy power would be provided in this Lightning Deep Fryer. Our company target for production in 2nd year we will target to increase it by RM 1 500,000. The management team in our company consist of several sections and is conducted by experienced employee to make sure our company is run efficiently.